THE ACTOR BETWEEN PRETENDED AND NON-PRETENDED PERFORMANCE IN THE THEATRICAL SHOW - Jawad Kazem Abboud Marwah; Zaid Thamer Abdulkadhim MuKhif (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The two researchers were interested in the study of (the theatrical actor between the artificial and the pretended performance in the theatrical performance), as the two researchers divided the topic of their research: Introduction to the research, which included the research problem and crystallized with the following question: (What is the artificial and non-artificial performance and how is the actor embodied in the theatrical performance?) The two researchers divided the topic of their research into three chapters: The first chapter deals with the fabricated and not the philosophically fabricated performance, as for the second chapter, it included the theater actor and directing experiences, and the third chapter contained an analytical study of the play (to stick ads), and the research was concluded with the conclusion - results - conclusions - List of sources and references